Copper adsorption behavior of three Malaysian rice soils - Choudhury, A.T.M.A.; Y., M. Khanif (Marcel Dekker, 2000)
Copper(Cu) deficiency exists in different rice growing areas of Malaysia. A study on Cu adsorption was carried out in three Malaysian rice soils (Idris, Tebengau, and Kangar series) using six levels of Cu (0, 100, 200, 300, 400, and 500 μg g-1). The data on Cu adsorption were fitted into Langmuir, Freundlich, and Temkin equations. Adsorption data were also correlated with pH, cation exchange capacity, and organic matter content of the soils. The effect of Cu addition on redox potential (Eh) of the soils was also measured. The Eh values were correlated with equilibrium solution Cu concentrations. Copper adsorption increased gradually with increasing level of added Cu in all the soils. The rate of increase was the highest in Kangar series followed by Tebengau and Idris, respectively. Correlation between Cu adsorption and pH was significant (r=0.772) whereas correlation of adsorption with either organic matter content or cation exchange capacity was nonsignificant. Copper adsorption in two soils (Idris and Tebengau) fitted Langmuir, Freundlich, and Temkin equations whereas Cu adsorption in the Kangar soil fitted Freundlich and Temkin equations. Redox potential (Eh) of the soils increased gradually with increasing level of added Cu. The rate of increase was the highest in Idris followed by Kangar and Tebengau soils, respectively. The relationship between equilibrium solution Cu concentration and redox potential was significant. The results of this study indicated that copper adsorption is mainly dependent on soil pH. In soils with higher adsorption capacity, more Cu fertilizer may be needed to get immediate crop response.